Career interest survey of secondary school students in Niger-delta region of Nigeria (2014)
The study examined the career interests of secondary school students in the Niger-Delta area of Nigeria. The survey research utilised qualitative and quantitative methods for data collection. A total of 860 (male-49.1%) female-50.9%) respondents attending private schools in Warri and Port-Harcourt participated in the study. Both descriptive and inferential methods were used for data analysis. Male students were found to be more interested in studying engineering related courses while the females showed greater interest in Health Sciences. Further analyses however) showed no significant difference based on gender in terms of pursuing a career interest. Most of the participants indicated course preference based on potential for financial benefits. It implies that career guidance and policy formulation need to consider interest as a factor in result oriented planning and intervention towards the educational development of the Niger-Delta